Green Technology for Business: A Bibliometric Analysis - I Gusti Ayu Agung Pradnya Dewi; Ngakan Nyoman Kutha Krisnawijaya; Putu Irma Yunita; Putu Dyah Permatha Korry (Binus Business Review, 2022)
Green technology has gained prominence this decade since the core of green technology preserves the resources and the environment while enhancing business sustainability. However, few pieces of research present literature reviews of the application of green technology for business despite its importance in providing the map of a conceptual framework for identifying research gaps, inconsistencies in prior studies, and the â€œstate-of-the-artâ€ snapshot domain for future research. The research contributed to the limited literature reviews regarding the application of green technology in business research by using a novel approach, which was bibliometric analysis. The research aimed to provide evidence of collaboration between authors and the most influential countries related to applying green technology for business research using co-authorship analysis. It also analyzed the knowledge structure of this topic and determined the primary and emerging issues through co-word analysis. Furthermore, the research performed the analysis of co-citation to identify the intellectual backbone of this research domain. On top of that, the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) approach was used to provide better accuracy in identifying and extracting the data for a bibliometric review. As the result, the research finds 735 journal articles related to green technology for business research from 1995 to 2020. In addition, four clusters are found to describe the current state of green technology for business research: environmental performance, circular economy, sustainable development, and climate policy. Then, research trend is also proposed to guide potential areas for further research to ascertain that the researchers have an inclusive insight on this topic.